"No(t) camping": engaging intersections of housing, transportation, and environmental justice through critical praxis. Issue 2 (2nd April 2020) - McGreavy, Bridie; Kelley, Scott; Ludden, Jason; Card, Daniel; Cogbill-Seiders, Elisa; Derk, Ian; Gordon, Constance; Haynal, Kaitlyn; Krzus-Shaw, Kassia; Parks, Melissa M.; Petts, Ashleigh; Ross, Derek G.; et al.
ABSTRACT: The Environmental Justice working group took an engaged and intersectional approach, focusing on interconnections between affordable housing, transportation, and University of Nevada, Reno campus planning. The working group made three recommendations to advance local environmental justice commitments: (1) improve air quality and access to green spaces in campus development, (2) prioritize affordable housing and civic engagement, and (3) uphold standards for equity and community collaborations. This essay describes the series of collaborative activities that allowed the working group to identify and prioritize those recommendations, followed by a reflection on how this process may help inform future public rhetoric efforts.